C‐reactive protein as a predictor of anastomotic leak in the first week after anterior resection for rectal cancer. (5th September 2017) - Reynolds, I. S.; Boland, M. R.; Reilly, F.; Deasy, A.; Majeed, M. H.; Deasy, J.; Burke, J. P.; McNamara, D. A.
Abstract: Aim: Anastomotic leak (AL) after anterior resection results in increased morbidity, mortality and local recurrence. The aim of this study was to assess the ability of C‐reactive protein (CRP) to predict AL in the first week after anterior resection for rectal cancer. Method: A retrospective review of a prospectively maintained database that included all patients undergoing anterior resection between January 2008 and December 2013 was performed. The ability of CRP to predict AL was assessed using area under the receiver–operating characteristics (AUC) curves. The severity of AL was defined using the International Study Group of Rectal Cancer (ISREC) grading system. Results: Two‐hundred and eleven patients were included in the study. Statistically significant differences in mean CRP values were found between those with and without an AL on postoperative days 5, 6 and 7. A CRP value of 132 mg/l on postoperative day 5 had an AUC of 0.75, corresponding to a sensitivity of 70%, a specificity of 76.6%, a positive predictive value of 16.3% and a negative predictive value of 97.5%. Multivariable analysis found that a CRP of > 132 mg/l on postoperative day 5 was the only statistically significant patient factor that was linked to an increased risk of AL (HR = 8.023, 95% CI: 1.936–33.238, P  = 0.004). Conclusion: Early detection of AL may minimize postoperative complications. CRP is a useful negative predictive test for the development of AL following anterior resection.